Construct validity of the elementary motor speed ability - Krug, J.; Wenzel, U.; Voß, G.; Kurth-Rosenkranz, R.; Witt, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Rapid movements are connected with many terms, like quickness, speed, agility and power. Sheppard & Young (2006) reported on many studies of rapid complex movements. Later they derived for the training of agility and speed the influence of perception and anticipation. Voss, Witt and Werthner (2007) found the existence of elementary motor speed ability. These authors arranged reaction time, frequency speed, acyclic speed during reactive movements and non-reactive movements from defined preliminary tension or relative rest as categories of the elementary motor speed ability. Wenzel (2013) defined on the example of plantar flexion the speed with non-reactive movements as arbitrarily initiated. The purpose of this study was to inspect this theoretical construct of four elementary motor speed ability factors with an empirical data set using a confirmatory factor analysis (CFA). Methods: First, with 78 students the reliability of 10 tests and 15 items were checked. Second, the construct validity with 214 students (95 women, age M = 21.54, SD = 2.47 and 114 men, age M = 22.39, SD = 2.64) were investigated, using the Maximum-Likelihood-Method (IBM SPSS Statistics, SPSS AMOS 21). The goodness-of-fit with the fit indices by Hu and Bentler (1999) were calculated. Results: The valid model is based on simple and complex reaction speed, frequency speed and arbitrarily initiated speed. The global fit indices of the model are chi square = 86,08, df = 85, p = 0,447; CFI = 0.99; RMSEA = 0,009; SRMR = 0,071. The local fit indices were used for improvement of the model fit. Correlations were complemented on the residual variance based on the modification indices. All demands by Hu and Bentler (1999) are fulfilled for a good model fit. Discussion: The reaction speed is integrated in a second order factor with the two factors simple and complex reaction speed. There is a middle correlation (r = 0.31) between the reaction speed and frequency speed (tapping tests). The arbitrarily initiated speed is an independent factor. For the reactive speed only the test drop jump could be used, therefore, a factor could not be proved. Further investigations into the validity of the elementary motor speed ability are in preparation.